The impact of songs with prosocial lyrics on implicit cognition and prosocial behavior: a prospective event-related brain potential study - Xu, Qiujian; Liu, Siqi; Li, Meihui; Wang, Xiaoyu; Li, Junrui; Yuan, Xinran; Yang, Miaomiao; Yang, Mingyi; Jiang, Zhenxu; Gou, Qiaoqiao; Liu, Ningning; Han, Jiaqi; et al. (Frontiers in Psychology, 2025)
BackgroundMusic with prosocial lyrics is a significant area of study in music psychology. Based on the General Learning Model, such music can effectively enhance prosocial behaviors. However, little is known about the neural correlates of the impact on prosocial behavior of short-term exposure to music with prosocial lyrics. Previous research has primarily used self-report measures to explore the relationship between music and prosocial cognition and behavior. However, these measures can be influenced by social desirability biases when dealing with sensitive issues such as moral behavior. The study of implicit cognition can effectively avoid these biases and has thus attracted widespread attention.ObjectiveThis study is the first to investigate the electrophysiological characteristics of the relationship between exposure to music with prosocial lyrics and enhanced altruistic behavior and to elucidate the effects of such music on implicit prosocial cognition.MethodsThis laboratory study will recruit 45 college students, who will be tasked with listening to either music with prosocial lyrics or neutral music. We will then use the Single Category Implicit Association Test (SC-IAT) paradigm combined with event-related potentials (ERP) to investigate the impact of music with prosocial lyrics on participants' implicit prosocial cognition and further reveal the predictive power of implicit cognition on prosocial behavior (measured by assessing the level of voluntary unpaid participation in subsequent experiments).ResultsThe findings of this study will provide neuroscientific evidence on how music with prosocial lyrics influences prosocial behavior through cognitive processes and clarify the effectiveness of music with prosocial lyrics in enhancing implicit prosocial cognition and behavior. In addition, these findings will not only deepen the understanding of the relationship between music and social behavior but also provide theoretical foundations and practical guidance for education, psychological interventions, and strategies to improve social behavior, thereby promoting the application of music in fostering social harmony.